PENGARUH IKLIM KOMUNIKASI ORGANISASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI SATUAN KERJA KEPATUHAN PT BANK CENTRAL ASIA TBK - Pratiwi Wulandari Priharjo (Jurnal Visi Komunikasi, 2022)
Communication climate can be a one of the most important influence in work productivity, because communication climate wil influences the effort of organization’s members. If communication climate is well conditioned, the organization’s members indirectly will form a mental attitude to improve a quality of life. A mental attitude will encourage improvement of work productivity. This was realized by Satuan Kerja Kepatuhan PT Bank Central Asia Tbk. They realized that to get job done responsibly to company and government institutions need support from organization’s environment as well. This research used quantitative explanative type of research, that used survey through questionnaire as many as 120 statements with total of population and sample as many as 40 respondent that all employees of Satuan Kerja Kepatuhan PT Bank Central Asia Tbk. The measurement of influence of the organizational communication climate on the work prodictivity used spearman correlation’s rank, analitazion of regression and t table. The result of this research indicate that 41 percents is obtained about influence the communication climate on the work productivity. While, the rest is idicate by other variables out of regression model. That means organizational communication climate has a role in creating work productivity’s employee of Satuan Kerja Kepatuhan PT Bank Central Asia Tbk.